'A contemptible movie now showing in Times Square': Cultural distinctions, space and taste in the exhibition of Snuff at the National Theatre. Issue 2 (1st October 2020) - Herron, Adam
This article considers the urban landscape of New York City's theatre district in the 1970s and how its identity as a contested space provides insight into key cultural shifts, including changes to the regulation of media, variance and convergence between industrial practices in the film industry, and discursive struggles between culture and capital. With many of the city's luxurious picture palaces converted into movie theatres with cheaper ticket prices and more genre fare in the wake of the Great Depression, critics sought to contain 'low' media such as horror and pornography to prevent their spread from grind houses to prestigious milieus. Using the case study of Snuff (The Findlays, 1976) and its run at the National Theatre on 44th Street and Broadway, I argue that dailies and trade publications were more concerned with the choice of exhibition venue than the content of the low-budget exploitation feature from Monarch Releasing Corporation. Consequently, objections to the film were informed by broader contexts of gentrification, tastemaking and cultural distinctions, with hyperbolic images of the imagined audiences for Snuff generated by tastemakers when they were unable to convincingly critique the National itself.